A nanodiamond-formulated plant protein induces robust immunity against porcine epidemic diarrhea virus in piglets - Ho, Thuong Thi; Tran, Hoai Thu; Nguyen, Phuong Minh Thi; Bui, Huyen Thi; Nguyen, Hien Thu Thi; Le, Thao Bich Thi; Pham, Minh Dinh; Hsiao, Wesley Wei-Wen; Nguyen, Dai Huu; Chu, Ha Hoang; Pham, Ngoc Bich; Hoang, Hang Thu Thi (Frontiers in Immunology, 2025)
Porcine epidemic diarrhea virus (PEDV) continues to be a major infectious threat in swine, especially endangering piglets. The COE and S1D domains have been identified as crucial antigens suitable for designing subunit vaccines. Nanodiamonds (NDs), owing to their biocompatibility, large surface area, and modifiable surfaces, have gained interest as novel carriers to improve recombinant protein vaccines. In this study, we transiently expressed a COE-S1D fusion protein containing the GCN4pII motif (COE-S1D-pII) in Nicotiana benthamiana. The recombinant protein was subsequently mixed with nanodiamonds at various mass ratios to form COE-S1D:ND complexes. SDS-PAGE and Western blot analyses identified the optimal ratio as 1:24 (w/w). Additional size, zeta and morphology characterization of these complexes was carried out. We then assessed the immune response of the COE-S1D:ND complex (1:24, w/w) in pregnant sows and their piglets, comparing it to the response induced by the free COE-S1D-pII protein. After administering a booster dose, the COE-S1D:ND mixture significantly enhanced PEDV-specific IgG and COE-S1D-specific IgA levels, as well as neutralizing antibody titers, as measured by ELISA and virus neutralization assays in their piglets. Overall, the results highlight that ND nanoparticles can strengthen both systemic and mucosal immunity, supporting the potential of using plant-produced COE-S1D-pII protein in combination with nanodiamonds as a next-generation subunit vaccine candidate against PEDV.